Removal of Crystal Violet Dye from Aqueous Solution Using Immobilized Spent Coffee Powder - Teoh, Jia-Jun; Ong, Siew-Teng; Ha, Sie-Tiong (Universitas Gadjah Mada, 2025)
In this work, the possibility of using immobilized spent coffee powder (ISCP) as an adsorbent for crystal violet (CV) adsorption from an aqueous solution was analyzed. The effect of process parameters such as pH, contact time, number of ISCP films, and initial CV concentrations on the removal of CV was studied. The optimum pH for the adsorption of CV was found to be at pH 7. The adsorption was rapid at the initial stage, and equilibrium was achieved in 100 min. The adsorption of CV increased with the increasing number of ISCP films. Characterization of ISCP was carried out by using FESEM and ATR-FTIR. Langmuir isotherm model can be used to explain the equilibrium data, and a maximum sorption capacity of 97.09 mg/g with a high coefficient of determination (R2) of 0.9986, was obtained. The experimental data were found to be fitted well into the pseudo-second-order kinetic model. From the Plackett-Burman results, both contact time and pH were identified as significant factors. Under the optimum experimental conditions based on RSM, the percentage uptake predicted by the model was in close agreement with the experimental values.